Monografía del género cubano Herpyza C. Wright (Leguminosae) y principales alteraciones de sus hábitat - Ángela Beyra Matos; Grisel Reyes Artiles; Laura Hernández Valdés (Anales del Jardín Botánico de Madrid)
A monograph of the monotypic genus Herpyza C. Wright (Leguminosae- Papilionoideae), endemic from Cuba, is presented. The species is restricted to the white sand habitats in Pinar del Río and Isla de la Juventud provinces, and threatened by human pressure over its habitats. According to the IUCN criteria the species is proposed as “Endangered” (EN). Its taxonomic isolation justifies a phylogenetic study using molecular markers that sheds light on the relationships of Herpyza with the remainder taxa in the Leguminosae, so far unknown.